A Family of Styrylcoumarins: Synthesis, Spectroscopic, Photophysical and Photochemical Properties. Issue 8 (20th June 2013) - Avó, João; Martins, Sérgio; Parola, A. Jorge; Lima, João C.; Branco, Paula S.; Prates Ramalho, João P.; Pereira, António
<x xml:space="preserve">Abstract</x> Keeping it in the family: A new family of 5‐styrylcoumarins exhibit E–Z isomerization around the CαCβ bond with large extinction coefficients, medium‐lived excited states, and moderate fluorescence quantum yields (see picture). The alteration of these photophysical properties is also corroborated by computational studies.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>